Negative electrode active material, preparation method thereof, and negative electrode and secondary battery containing the negative electrode active material

By using a combination of silicon-based core particles and graphene external carbon coating with a D/G ratio of 0.35 or less in the negative electrode active material of lithium secondary batteries, the electrical contactability of silicon-based active materials caused by volume expansion/contraction is solved. The problem of deterioration and deterioration of high-temperature storage characteristics achieves longer life and more stable battery performance.

CN114424364BActive Publication Date: 2025-02-25LG ENERGY SOLUTION LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080066324.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-01
Filing Date
2020-10-30
Publication Date
2025-02-25
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

The silicon-based active material deteriorates electrical contact due to volume expansion/contraction in lithium secondary batteries, which reduces life characteristics, and reacts side effects with the electrolyte, deteriorating the high-temperature storage characteristics.

Method used

A negative electrode active material containing silicon-based core particles and an external carbon coating formed on the silicon-based core particles is used, and the external carbon coating is composed of graphene with a D/G ratio of 0.35 or less, and a composite material is formed by heat treatment.

Benefits of technology

Effectively prevent the deterioration of electrical contact between active materials, improve the life characteristics, and prevent side reactions with the electrolyte, thereby improving the high-temperature storage characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114424364B_ABST
    Figure CN114424364B_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode active material, comprising: a silicon-based core particle; and an outer carbon coating formed on the silicon-based core particle, wherein the outer carbon coating comprises graphene having a D / G ratio of 0.35 or less in a Raman spectrum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2019-0138874 filed in the Korean Intellectual Property Office on November 1, 2019, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The invention relates to a negative electrode active material and a preparation method thereof, as well as a negative electrode and a lithium secondary battery comprising the negative electrode active material. Background Art

[0005] Recently, due to the rapid popularization of electronic devices (such as mobile phones, laptops, electric vehicles, etc.) using batteries, the demand for small and lightweight secondary batteries with relatively high capacity has increased rapidly. In particular, lithium secondary batteries are lightweight and have high energy density, so they are attracting attention as driving power sources for portable devices. Therefore, research and development work for improving the performance of lithium secondary batteries has been actively carried out.

[0006] Generally, a lithium secondary battery comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, an electrolyte, an organic solvent, etc. In addition, the positive electrode and the negative electrode may have an active material layer on the current collector, and the active material layer comprises a positive electrode active material or a negative electrode active material. In the positive electrode, a lithium-containing metal oxide (such as LiCoO2 and LiMn2O4) is used as a positive electrode active material, and correspondingly in the negative electrode, a carbon-based active material or a silicon-based active material that does not contain lithium is used as a negative electrode active material.

[0007] In particular, among negative electrode active materials, silicon-based active materials have attracted much attention because their capacity is about 10 times higher than that of carbon-based negative electrode active materials, and due to their high capacity, silicon-based active materials have the advantage of being able to obtain high energy density even with thin electrodes. However, silicon-based active materials have problems in that the life characteristics are reduced due to the volume expansion / contraction with charge and discharge, and the high-temperature storage characteristics are deteriorated due to side reactions with the electrolyte during high-temperature storage.

[0008] Therefore, there is a need to develop a secondary battery capable of improving life characteristics and high-temperature storage characteristics while achieving high capacity and high energy density of silicon-based active materials.

[0009] Korean Patent Publication No. 10-2017-0074030 relates to a negative electrode active material for a lithium secondary battery, a preparation method thereof, and a lithium secondary battery comprising the same, and discloses a negative electrode active material comprising a porous silicon-carbon composite. However, there are limitations in solving the above problems.

[0010] [Prior art documents]

[0011] [Patent document]

[0012] Korean Patent Publication No. 10-2017-0074030 Summary of the invention

[0013] Technical issues

[0014] One aspect of the present invention provides a negative electrode active material capable of effectively preventing deterioration of electrical contact between active materials due to volume expansion / contraction of the active materials and improving life characteristics when a silicon-based active material is used.

[0015] Another aspect of the present invention provides a negative electrode active material capable of preventing a side reaction with an electrolyte and improving high temperature storage characteristics when a silicon-based active material is used.

[0016] Another aspect of the present invention provides a method for preparing the above negative electrode active material.

[0017] Another aspect of the present invention provides a negative electrode and a secondary battery comprising the negative electrode active material.

[0018] Technical Solution

[0019] According to one aspect of the present invention, there is provided a negative electrode active material comprising a silicon-based core particle and an outer carbon coating formed on the silicon-based core particle, wherein the outer carbon coating comprises graphene having a D / G ratio of 0.35 or less in a Raman spectrum, and the D / G ratio in the Raman spectrum is represented by the following formula 1:

[0020] [Formula 1]

[0021] D / G = D band peak intensity / G band peak intensity.

[0022] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned negative electrode active material, wherein the method comprises mixing silicon-based core particles and graphene flakes, and subjecting the mixture to heat treatment.

[0023] According to another aspect of the present invention, a negative electrode is provided, comprising a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode material, a binder and a conductive material, and the negative electrode material contains the above-mentioned negative electrode active material.

[0024] According to another aspect of the present invention, there is provided a secondary battery including the above-mentioned negative electrode, a positive electrode opposite to the negative electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte.

[0025] Beneficial Effects

[0026] The negative electrode active material of the present invention comprises an outer carbon coating formed on a silicon-based core particle, and the outer carbon coating comprises graphene having a D / G ratio in a specific range in Raman spectrum. The graphene used in the negative electrode active material of the present invention has few defects and excellent conductivity, so that even if the silicon-based active material has volume expansion / contraction, the electrical contact between the active material and the active material or between the active material and the current collector can be smoothly maintained.

[0027] In addition, the negative active material of the present invention includes graphene having a D / G ratio within a specific range in the outer carbon coating layer, and thus can prevent a side reaction with an electrolyte and improve high temperature storage characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The following drawings attached to this specification illustrate preferred embodiments of the present invention by way of example, and together with the detailed contents of the present invention given below, help to further understand the technical concept of the present invention. Therefore, the present invention should not be interpreted solely by the matters in such drawings.

[0029] Figure 1 is a photograph of the negative electrode active material prepared in Example 1 observed by a scanning electron microscope (SEM). DETAILED DESCRIPTION

[0030] It should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to the meanings defined in commonly used dictionaries. It should also be understood that based on the principle that the inventor can appropriately define the meaning of words or terms to best explain the invention, the words or terms should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology and the technical concept of the present invention.

[0031] The terms used herein are only used to describe specific exemplary embodiments and are not intended to limit the present invention. Terms in the singular may include plural forms unless the context clearly indicates otherwise.

[0032] It should also be understood that the terms "include", "comprises" or "has" used in this specification specify the presence of the stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.

[0033] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the volume accumulation in the particle size distribution curve. The average particle size (D 50) can be measured by, for example, laser diffraction. Laser diffraction is generally capable of measuring particle sizes from the submicron region to several millimeters, thereby enabling highly reproducible and high-resolution results to be obtained.

[0034] Hereinafter, the present invention will be described in detail.

[0035] <Negative Electrode Active Material>

[0036] The present invention relates to a negative electrode active material which can be preferably used in a lithium secondary battery.

[0037] The negative electrode active material of the present invention comprises a silicon-based core particle and an outer carbon coating formed on the silicon-based core particle, wherein the outer carbon coating comprises graphene having a D / G ratio of 0.35 or less in a Raman spectrum, and the D / G ratio in the Raman spectrum is represented by the following formula 1:

[0038] [Formula 1]

[0039] D / G = D band peak intensity / G band peak intensity.

[0040] Generally, it is known that the capacity of silicon-based active materials is about 10 times higher than that of carbon-based active materials. Therefore, when silicon-based active materials are applied to the negative electrode, it is expected that a thin film electrode with a high energy density level can be achieved. However, silicon-based active materials have problems of electrical short circuit and life degradation due to volume expansion / contraction caused by lithium insertion / extraction accompanying charging and discharging. In particular, when the silicon-based active material undergoes volume expansion / contraction due to charging and discharging, the distance between the active materials increases, resulting in poor electrical contact and electrical short circuit. As a result, the path for the movement of charges is lost and lithium ions are isolated, which can lead to a rapid deterioration of the life of the negative electrode and a reduction in capacity.

[0041] In order to solve the above limitations, the negative electrode active material of the present invention comprises a silicon-based core particle and an external carbon coating formed on the silicon-based core particle, wherein the external carbon coating comprises graphene with a D / G ratio of less than 0.35. Graphene with a D / G ratio in the above range has few defects and excellent conductivity, and therefore, when applied to the external carbon coating, the initial efficiency of the negative electrode active material can be improved, and despite the expansion / contraction of the silicon-based core particles, the electrical contact can still be maintained or improved, so that the life characteristics can be improved at an excellent level. In addition, the external carbon coating containing graphene with a D / G ratio in the above range can prevent side reactions with the electrolyte at an excellent level, and thus improve the high temperature storage characteristics of the negative electrode active material.

[0042] The silicon-based core particle is capable of intercalating / deintercalating lithium, and the silicon-based core particle may be used as a core particle of a negative electrode active material.

[0043] The silicon-based core particle may include a silicon-based material represented by the following Chemical Formula 1, and at least one metal included in the silicon-based material and selected from the group consisting of Li, Mg, and Al.

[0044] [Chemical formula 1]

[0045] SiO x

[0046] In the above Chemical Formula 1, 0≤x<2.

[0047] In the above chemical formula 1, SiO2 (when x=2 in the above chemical formula 1) does not react with lithium ions and thus cannot store lithium, so x is preferably within the above range. Specifically, in the above chemical formula 1, x may be 0.5≤x≤1.5 in terms of structural stability of the active material.

[0048] The metal is contained in the silicon-based material, and the metal is at least one selected from the group consisting of Li and Mg. The metal may be contained so as to improve the efficiency of the active material by reducing the ratio of the irreversible phase of the silicon-based core particle (e.g., SiO2), and may be at least one selected from the group consisting of Li, Mg, and Al, preferably at least one selected from the group consisting of Li and Mg, more preferably Mg.

[0049] The metal may be contained in the silicon-based core particle in an amount of 1 wt % to 30 wt %, preferably 3 wt % to 20 wt %, and within the above range, the capacity and efficiency of the silicon-based core particle can be simultaneously improved to desired levels, which is therefore preferred.

[0050] The silicon-based core particles may be a mixture of Si, SiO2 and metal silicate, wherein the metal silicate contains at least one metal selected from the group consisting of Li, Mg and Al. For example, the metal in the silicon-based core particles may react with the silicon oxide in the silicon-based core particles and exist in the form of metal silicate.

[0051] The average particle size (D) of the silicon-based core particles is preferably 0.1-1.0mm in diameter and 0.1-1.0mm in diameter, in terms of ensuring the structural stability of the active material during charge and discharge, preventing an increase in the level of volume expansion / contraction due to an excessive increase in particle size, and preventing a decrease in initial efficiency due to an excessively small particle size. 50 ) can be 0.5 μm to 20 μm, preferably 1 μm to 10 μm.

[0052] The silicon-based core particles may be contained in the negative electrode active material in an amount of 80 wt % to 99.9 wt %, preferably 85 wt % to 95 wt %. When within the above range, it is preferred in terms of improving the capacity of the negative electrode, and accordingly, the effect of preventing electrical short circuits by the external carbon coating described later, the improvement of conductivity, and the improvement of life characteristics can be more preferably achieved.

[0053] The outer carbon coating is formed on the silicon-based core particle.

[0054] The outer carbon coating layer includes graphene having a D / G ratio in Raman spectrum of 0.35 or less, and the D / G ratio in Raman spectrum is represented by the following formula 1:

[0055] [Formula 1]

[0056] D / G = D band peak intensity / G band peak intensity.

[0057] The D / G ratio is used as an indicator to evaluate the defects or crystallinity of graphene. -1 The G band peaks near the carbon are attributed to the sp 2 Coupled E 2g Vibration mode, 1350cm -1 The D band peak near the carbon sp 2 Occurs when there is a defect in the coupling.

[0058] The external carbon coating of the present invention comprises graphene with a D / G ratio of less than 0.35, and therefore, it is possible to achieve graphene with few defects and excellent conductivity. Therefore, the external carbon coating of the present invention can prevent the problem of electrical short circuit caused by the expansion / contraction of the silicon-based core particles, thereby improving the life performance of the battery and improving the initial efficiency. In addition, when the graphene with a D / G ratio in the above range is used as a component of the external carbon coating, the defects of the graphene material are few, so that the side reaction with the electrolyte can be prevented at an excellent level, and the high temperature storage characteristics of the negative electrode active material can be improved accordingly. If a graphene with a D / G ratio greater than 0.35 is used, the defects in the graphene will increase, thereby reducing the conductivity, making it impossible to prevent the problem of electrical short circuit of the silicon-based core particles, and it is impossible to expect the life performance to be improved.

[0059] The D / G ratio of the graphene may be below 0.35, preferably 0.01 to 0.35, and more preferably 0.05 to 0.25, and when within the above range, the deterioration of the dispersibility and coating performance of the graphene due to excessive reduction in the D / G ratio can be prevented to further improve the above-mentioned life performance, initial efficiency, conductivity and high-temperature storage characteristics.

[0060] When graphene is prepared by using a high-pressure homogenizer, the D / G ratio of the graphene can be achieved by appropriately controlling the number of times the graphite material as the graphene raw material passes and circulates in the microchannel in the high-pressure homogenizer, the applied pressure in the high-pressure homogenizer, and the speed and time of passing through the microchannel.

[0061] The thickness of the outer carbon coating layer may be 10 nm to 500 nm, preferably 30 nm to 200 nm, and when within the above range, the capacity of the negative electrode active material can be prevented from being reduced due to excessive increase in thickness, the side reaction with the electrolyte can be prevented at a more desirable level, and the electrical short circuit problem of the silicon-based core particles can be prevented. For example, the thickness of the outer carbon coating layer can be measured by a transmission electron microscope (TEM).

[0062] The outer carbon coating may be contained in the negative electrode active material in an amount of 1 wt % to 25 wt %, preferably 3 wt % to 15 wt %, and more preferably 6 wt % to 12 wt %. Within the above range, the capacity of the negative electrode active material can be prevented from being reduced due to excessive increase in the content of the outer carbon coating, a side reaction with the electrolyte can be prevented at a more desirable level, and an electrical short circuit problem of the silicon-based core particles can be prevented.

[0063] The negative electrode active material of the present invention may further include an inner carbon coating formed between the silicon-based core particle and the outer carbon coating. The inner carbon coating can suppress the volume expansion of the silicon-based core particle and can serve as a protective layer for further preventing side reactions with the electrolyte.

[0064] Based on the weight of the silicon-based core particles and the internal carbon coating, the internal carbon coating can be included in an amount of 1 wt % to 10 wt %, preferably 3 wt % to 7 wt %. When within the above range, the internal carbon coating can prevent side reactions with the electrolyte while controlling the volume expansion of the silicon-based core particles at an excellent level, and is therefore preferred.

[0065] The inner carbon coating layer may be an amorphous carbon coating layer. Specifically, the inner carbon coating layer may be formed by a chemical vapor deposition (CVD) method using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene.

[0066] <Method for preparing negative electrode active material>

[0067] In addition, the present invention provides a method for preparing the above-mentioned negative electrode active material.

[0068] Specifically, the method for preparing the negative electrode active material of the present invention includes mixing silicon-based core particles and graphene sheets, and subjecting the mixture to heat treatment.

[0069] The method for preparing a negative electrode active material of the present invention comprises mixing silicon-based core particles and graphene sheets.

[0070] The silicon-based core particles have been described above.

[0071] The graphene sheets may be mixed with the silicon-based core particles and then heat-treated to become a component of an outer carbon coating.

[0072] Specifically, the graphene sheet can be prepared by a method comprising the following steps.

[0073] (a) forming a dispersion liquid containing a graphite-based material and a dispersant; and

[0074] (b) allowing the dispersion to continuously pass through a high-pressure homogenizer via an inlet of the high-pressure homogenizer, wherein the high-pressure homogenizer includes an inlet, an outlet, and a microchannel connecting the inlet and the outlet, thereby exfoliating graphene sheets in the graphite-based material.

[0075] According to the above method, graphene sheets can be peeled off from graphite materials by shear force in a high-pressure homogenizer. In the case of the above method, the process of graphene peeling is simplified, and processes such as acid treatment that cause defects in graphene are not involved, so that graphene with fewer defects can be prepared. In addition, in the case of the above method, compared with a method of peeling graphene by ultrasonic treatment, a method of obtaining graphene by preparing graphite oxide and reducing it, etc., the advantage is that graphene has fewer defects and excellent conductivity. Therefore, when the outer carbon coating of the negative active material is formed by the graphene sheets obtained by the above method, the conductivity can be improved while preventing the electrical short circuit of the silicon-based core particles at an excellent level, thereby improving the life characteristics.

[0076] The method for preparing a graphene sheet includes (a) forming a dispersion liquid including a graphite-based material and a dispersant.

[0077] The dispersion may be a dispersion in which the graphite material and the dispersant are dissolved or dispersed in an aqueous solvent or a polar organic solvent. The aqueous solvent or the polar organic solvent may be one or more selected from the group consisting of water, NMP, acetone, N,N dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, methanol, butanol, 2-ethoxyethanol, 2-butoxyethanol, 2-methoxypropanol, tetrahydrofuran (THF), ethylene glycol, pyridine, dimethylacetamide, N-vinyl pyrrolidone, methyl ethyl ketone (methyl ethyl ketone), α-terpineol, formic acid, ethyl acetate and acrylonitrile.

[0078] The graphite-based material is a raw material of graphene sheets, and may be, for example, plate-like graphite.

[0079] As the dispersant, any known material for uniformly dispersing various carbon-based materials in polar solvents can be used, such as tannic acid, polyacrylic acid, Triton X-100 (trade name), or Pluronics F-127 (trade name), etc. However, more suitably, a dispersant can be used, which is a mixture of a plurality of polycyclic aromatic hydrocarbon oxides and contains a polycyclic aromatic hydrocarbon oxide having a molecular weight of about 300 to 1000, preferably 300 to 700, in which the content is about 60% by weight or more, preferably 65% ​​by weight or more, and more preferably 70% by weight to 95% by weight. Specifically, the dispersant can be polyacrylic acid.

[0080] The method for preparing graphene sheets comprises (b) allowing a dispersion to continuously pass through a high-pressure homogenizer via an inlet of the high-pressure homogenizer, wherein the high-pressure homogenizer comprises an inlet, an outlet, and a microchannel connecting the inlet and the outlet, thereby exfoliating graphene sheets in a graphite-based material.

[0081] The high-pressure homogenizer may include an inlet into which the dispersion is injected; a microchannel through which the injected dispersion continuously passes; and an outlet from which the graphene sheets prepared in the microchannel are obtained. The graphite-based material may be exfoliated through the microchannel under the action of shear force, thereby forming a graphene sheet having a nanometer-scale thickness. When the graphene sheet is prepared in the high-pressure homogenizer, the graphene sheet can be continuously obtained without a separate pretreatment process, thereby making it possible to mass-produce graphene sheets without defects and thus having excellent conductivity.

[0082] The dispersion may be introduced into the inlet of the high pressure homogenizer at a pressure of 100 bar to 3000 bar, more preferably 500 bar to 1500 bar, and pass through the microchannel. When the dispersion passes through the microchannel within the above pressure range, the passing speed of the dispersion increases due to the high pressure, so that a high shear force can be obtained, and accordingly, the exfoliation of the graphene sheet can be achieved without defects.

[0083] The diameter of the microchannel may be about 1 mm or less, preferably 10 μm to 800 μm, and when the dispersion passes through the microchannel within the above range, a high shear force may be achieved. Such a shear force facilitates the peeling of carbon atom layers in which carbon atoms are bonded by van der Waals bonds rather than in the basal plane of the graphite-based material forming a covalent bond, so that a thin graphene sheet with few defects can be effectively formed.

[0084] In the above method, the D / G ratio of the graphene sheet can be controlled to be below 0.35, preferably 0.01 to 0.35, and more preferably 0.05 to 0.25 by appropriately controlling the number of microchannel cycles in the high-pressure homogenizer, the applied pressure, and the speed and time of passing through the microchannel.

[0085] The method of preparing the negative electrode active material of the present invention includes subjecting the mixture to heat treatment.

[0086] According to the preparation method of the present invention, the composite of the silicon-based core particles and the graphene sheets can be performed through a heat treatment step, and thus, an outer carbon coating layer containing graphene can be formed on the silicon-based core particles.

[0087] Specifically, the heat treatment can be performed by spray drying. The spray drying process is a method for preparing a dry powder by spraying a liquid feed and rapidly heat treating or drying it with hot gas. It is preferred that the negative electrode active material of the present invention be heat treated by the above-mentioned spray drying process because the mixture can be rapidly heat treated or dried, thereby preventing agglomeration between particles and improving the quality uniformity of the negative electrode active material.

[0088] Specifically, the heat treatment may be performed by injecting an inert gas at 150° C. to 350° C. into the drying chamber while spraying the mixture into the drying chamber.

[0089] In the spray drying process, the inert gas is a non-reactive gas and may be at least one of the group preferably consisting of helium, nitrogen and argon.

[0090] In the spray drying process, the temperature of the inert gas may be 150° C. to 350° C., preferably 180° C. to 250° C. When the heat treatment is performed within the above range, drying of the mixture is promoted, and a negative active material having improved quality uniformity may be prepared.

[0091] The method for preparing a negative electrode active material of the present invention may further include forming an inner carbon coating on the silicon-based core particles before mixing the silicon-based core particles and the graphene sheets. The inner carbon coating may be formed on the silicon-based core particles to suppress the volume expansion of the silicon-based core particles due to charge and discharge, and to serve as a protective layer to prevent side reactions with the electrolyte.

[0092] The step of forming the inner carbon coating layer can be implemented by a chemical vapor deposition (CVD) method, specifically, can be implemented by a chemical vapor deposition (CVD) method using at least one hydrocarbon gas selected from the group consisting of methane, ethane and acetylene. According to the above method, the inner carbon coating layer can be formed on the silicon-based core particles at a uniform level, so that the volume expansion of the silicon-based core particles can be smoothly controlled and the side reaction caused by the electrolyte can be prevented.

[0093] The step of forming the inner carbon coating layer may be performed at 800°C to 1100°C, preferably 900°C to 1000°C.

[0094] Additional description of the internal carbon coating has been given above.

[0095] <Negative electrode>

[0096] In addition, the present invention also provides a negative electrode comprising the negative electrode active material.

[0097] Specifically, the negative electrode of the present invention comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode material, a binder and a conductive material, and the negative electrode material comprises the above-mentioned negative electrode active material.

[0098] The negative electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. Specifically, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used as the negative electrode current collector.

[0099] The thickness of the negative electrode current collector may generally be 3 μm to 500 μm.

[0100] The negative electrode current collector may have fine concavoconvexities formed on its surface to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven fabric body.

[0101] The negative electrode active material layer is formed on the negative electrode current collector.

[0102] The negative electrode active material layer may include a negative electrode material and a binder, and the negative electrode material includes the negative electrode active material described above.

[0103] The negative electrode active material may be included in the negative electrode to show excellent capacity characteristics, and may contribute to improving life characteristics of the negative electrode by using graphene having a D / G ratio within the above range as a coating component.

[0104] The negative electrode active material has been described above.

[0105] The negative electrode material may further include a carbon-based active material in addition to the above-mentioned negative electrode active material. Therefore, the carbon-based active material having a low volume expansion degree during charge and discharge can reduce the volume expansion degree of the entire negative electrode material and is more preferred for improving resistance and efficiency.

[0106] The carbon-based active material may include at least one selected from the group consisting of artificial graphite, natural graphite, hard carbon, soft carbon, carbon black, acetylene black, Ketjen black, Super P, graphene and fibrous carbon, and may preferably include at least one selected from the group consisting of artificial graphite and natural graphite.

[0107] In terms of ensuring structural stability during charge and discharge and reducing side reactions with the electrolyte, the average particle size (D 50) can be 5 μm to 35 μm, preferably 10 μm to 20 μm.

[0108] Specifically, in terms of improving both capacity performance and cycle performance, the negative electrode material preferably uses both the negative electrode active material and the carbon-based active material. Specifically, it is preferred that the negative electrode material contains the negative electrode active material and the carbon-based active material in a weight ratio of 1:99 to 35:65, preferably 5:95 to 30:70, and more preferably 10:90 to 20:80. When within the above range, it is preferred in terms of improving both capacity and cycle performance.

[0109] The negative electrode material may be included in the negative electrode active material layer in an amount of 80 wt % to 99 wt %, preferably 90 wt % to 98.5 wt %.

[0110] The negative electrode active material layer includes a binder.

[0111] In terms of further improving electrode adhesion and imparting sufficient volume expansion / contraction resistance to the active material, the binder may include at least one selected from the group consisting of styrene-butadiene rubber (SBR), nitrile rubber, acrylic rubber, butyl rubber, fluororubber, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG), polyacrylonitrile (PAN) and polyacrylamide (PAM). Preferably, in terms of having high strength, excellent resistance to volume expansion / contraction of silicon-based active materials, and imparting excellent flexibility to the binder to prevent distortion, bending, etc. of the electrode, the binder preferably includes styrene-butadiene rubber.

[0112] The binder may be included in the negative electrode active material layer in an amount of 0.5 wt % to 10 wt %. Within the above range, it is preferred in terms of more effectively controlling volume expansion of the active material.

[0113] If necessary, the negative electrode active material layer may further include a conductive material. The conductive material may be used to improve the conductivity of the negative electrode, and preferably has conductivity without causing chemical changes. Specifically, the conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black, conductive fiber, fluorocarbon powder, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and may preferably include carbon black in terms of achieving high conductivity.

[0114] The conductive material may be included in the negative active material layer in an amount of 0.5 wt % to 10 wt %.

[0115] In terms of increasing the electrical contact of the negative electrode material components due to the above-mentioned SWCNT and the like, the negative electrode active material layer may be 30 μm to 100 μm, preferably 40 μm to 80 μm.

[0116] The negative electrode may be manufactured by dispersing a negative electrode material, a binder, and a conductive material in a solvent for forming a negative electrode slurry to prepare a negative electrode slurry, coating the negative electrode slurry on a negative electrode collector, and then drying and roll-pressing.

[0117] In terms of promoting dispersion of components, the negative electrode slurry-forming solvent may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, preferably distilled water.

[0118] <Secondary Battery>

[0119] The present invention provides a secondary battery comprising the negative electrode, specifically, a lithium secondary battery.

[0120] Specifically, the secondary battery according to the present invention includes the above-mentioned negative electrode, a positive electrode opposite to the negative electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte.

[0121] The positive electrode may include a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector.

[0122] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. Specifically, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used as the positive electrode current collector.

[0123] The thickness of the positive electrode current collector may generally be 3 μm to 500 μm.

[0124] The positive electrode current collector may have fine concavoconvexities formed on its surface to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven fabric body.

[0125] The positive electrode active material layer may include a positive electrode active material.

[0126] The positive electrode active material is a compound capable of reversibly inserting and deinserting lithium, specifically, it may include a lithium transition metal composite oxide, wherein the lithium transition metal composite oxide includes at least one transition metal selected from the group consisting of nickel, cobalt, manganese, and aluminum and lithium. Preferably, the lithium transition metal composite oxide includes a transition metal containing nickel, cobalt or manganese and lithium.

[0127] More specifically, the lithium transition metal composite oxide may be a lithium manganese oxide (e.g., LiMnO2, LiMn2O4, etc.), a lithium cobalt oxide (e.g., LiCoO2, etc.), a lithium nickel oxide (e.g., LiNiO2, etc.), a lithium nickel manganese oxide (e.g., LiNi 1-Y Mn Y O2 (where 0 <Y<1)、LiMn 2-z Ni z O4 (where 0<Z<2), etc.), lithium nickel cobalt oxides (such as LiNi 1-Y1 Co Y1 O2 (where 0<Y1<1), etc.), lithium manganese cobalt oxides (such as LiCo 1-Y2 Mn Y2 O2 (where 0<Y2<1), LiMn 2-z1 Co z1 O4 (where 0<Z1<2), etc.), lithium nickel manganese cobalt oxides (such as Li(Ni p Co q Mn r1 )O2 (where 0<p<1, 0<q<1, 0<r1<1, p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0<p1<2, 0<q1<2, 0<r2<2, p1+q1+r2=2), etc.), or lithium nickel cobalt transition metal (M) oxide (such as Li(Ni p2 Co q2 Mn r3 A S2 )O2 (wherein M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo, and p2, q2, r3 and s2 are each the atomic fractions of independent elements, and 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, p2+q2+r3+s2=1), etc.), etc., and may contain any one of them or a mixture of two or more thereof. Among them, in terms of being able to increase the capacity and stability of the battery, the lithium transition metal composite oxide may be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, or Li(Ni 0.8 Mn 0.1 Co 0.1)O2, etc.) or lithium nickel cobalt aluminum oxide (e.g. Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc. When considering the significant improvement effect according to the control of the type and content ratio of the constituent elements forming the lithium transition metal composite oxide, the lithium transition metal composite oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2、Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc., any one of them or a mixture of two or more thereof can be used.

[0128] In consideration of sufficient capacity development of the positive electrode active material, the positive electrode active material may be contained in the positive electrode active material layer in an amount of 80 wt % to 99 wt %, preferably 92 wt % to 98.5 wt %.

[0129] The positive electrode active material layer may further include a binder and / or a conductive material in addition to the positive electrode active material.

[0130] The binder is a component used to assist the bonding of active materials, conductive materials, etc. and to the collector, and specifically may include at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber and fluororubber, preferably polyvinylidene fluoride.

[0131] The binder may be contained in the positive electrode active material layer in an amount of 1 to 20 wt %, preferably 1.2 to 10 wt %, in terms of ensuring sufficient binding force between components such as the positive electrode active material.

[0132] The conductive material can be used to assist and improve the conductivity in the secondary battery, and is not particularly limited as long as it has conductivity and does not cause chemical changes. Specifically, the conductive material may include graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbon powder; metal powders such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and may preferably include carbon black in terms of improving conductivity.

[0133] In terms of ensuring sufficient conductivity, the conductive material may be contained in the positive electrode active material layer in an amount of 1 wt % to 20 wt %, preferably 1.2 wt % to 10 wt %.

[0134] The thickness of the positive electrode active material layer may be 30 μm to 400 μm, preferably 50 μm to 110 μm.

[0135] The positive electrode may be manufactured by coating a positive active material slurry including a positive active material and optionally a binder, a conductive material, and a solvent for forming the positive electrode slurry on a positive electrode current collector, followed by drying and roll pressing.

[0136] The positive electrode slurry forming solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount such that a preferred viscosity is achieved when the positive electrode active material and an optional binder, a conductive material, etc. are included. For example, the positive electrode slurry forming solvent may be included in the positive electrode slurry in an amount such that the concentration of the solid containing the positive electrode active material and the optional binder and conductive material is 50 wt % to 95 wt %, preferably 70 wt % to 90 wt %.

[0137] The separator is used to separate the negative electrode and the positive electrode, and to provide a mobile path for lithium ions. Any separator can be used without particular limitation, as long as it is a separator commonly used in secondary batteries. In particular, it is preferred to have excellent electrolyte moisture retention and a separator with low resistance to ion movement in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin-based polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of glass fiber, polyethylene terephthalate fiber, etc. having a high melting point. In addition, a coated separator comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multilayer structure.

[0138] In addition, the electrolyte used in the present invention may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used in the manufacture of a secondary battery, but is not limited thereto.

[0139] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0140] Any organic solvent can be used without particular limitation, as long as it can serve as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as an organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. In the above-mentioned solvent, carbonate solvent is preferred, more preferably a mixture of cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) with high ion conductivity and high dielectric constant and low viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) which can increase the charge and discharge performance of the battery. In this case, when cyclic carbonate and linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte may be excellent.

[0141] Any compound can be used as a lithium salt without special restrictions, as long as it can provide lithium ions used in lithium secondary batteries. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. The lithium salt can be used in a concentration range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby showing excellent performance, and lithium ions can be effectively moved.

[0142] According to a typical method of manufacturing a secondary battery, the secondary battery may be manufactured by inserting a separator between the above-mentioned negative electrode and positive electrode and then injecting an electrolyte therein.

[0143] The secondary battery according to the present invention can be used in portable devices such as mobile phones, notebook computers and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEV), and in particular, can be preferably used as a component battery of a medium-to-large battery module. Therefore, the present invention also provides a medium-to-large battery module, comprising the secondary battery as described above as a unit cell.

[0144] The medium and large-sized battery module as described above may be preferably applied to power sources requiring high output and large capacity, such as electric vehicles, hybrid electric vehicles, and energy storage devices.

[0145] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.

[0146] Example

[0147] Example 1: Preparation of negative electrode active material

[0148] <Preparation of graphene sheets>

[0149] Plate-like graphite as a graphite-based material and polyacrylic acid as a dispersant were dispersed in water at a weight ratio of 95:5 to prepare a dispersion (solid content: 5% by weight).

[0150] Under a pressure of 1000 bar, 1L of the dispersion was introduced into the inlet of a high-pressure homogenizer, wherein the high-pressure homogenizer comprises the inlet, the outlet and a microchannel (diameter: 100 μm) connecting the inlet and the outlet, and the dispersion was passed through the microchannel at a speed of 100 m / s and circulated for 30 minutes. Through the above, the plate-like graphite was peeled off to prepare a graphene sheet.

[0151] The D / G ratio of the graphene sheet prepared above was calculated by Raman spectrum of a Raman spectrometer (trade name: Microscope Raman, manufacturer: Almega XR) (D / G ratio=0.2).

[0152] <Preparation of negative electrode active material>

[0153] As silicon-based core particles, SiO particles (average particle size (D 50 ): 6 μm). The silicon-based core particles contain Mg in an amount of 5 wt% based on the total weight, and the silicon-based core particles are a mixture of Si, SiO2, and magnesium silicate (MgSiO3 and / or Mg2SiO4).

[0154] Methane was chemically vapor deposited (CVD) as a hydrocarbon gas on the silicon-based core particles at 950° C. to form an inner carbon coating on the silicon-based core particles. The inner carbon coating was formed at 5 wt % based on the total weight of the silicon-based core particles and the inner carbon coating.

[0155] The silicon-based core particles having an inner carbon coating layer and the graphene sheets were mixed at a weight ratio of 95:5.

[0156] The mixture is heat-treated by a spray drying method. Specifically, the mixture is sprayed into a drying chamber by a sprayer, and argon gas at 200°C is injected into the drying chamber to rapidly heat-treat the mixture, and the heat-treated mixture is recovered to prepare the negative electrode active material of Example 1. The negative electrode active material comprises a silicon-based core particle and an inner carbon coating formed on the silicon-based core particle, and an outer carbon coating formed on the inner carbon coating, wherein the outer carbon coating comprises graphene having a D / G ratio of 0.2. The outer carbon coating is contained in the negative electrode active material in an amount of 5% by weight.

[0157] Example 2: Preparation of negative electrode active material

[0158] The negative electrode active material of Example 2 was prepared in the same manner as in Example 1, except that the silicon-based core particles having an inner carbon coating layer and the graphene sheet were mixed at a weight ratio of 90:10. In this negative electrode active material, the outer carbon coating layer was contained in the negative electrode active material in an amount of 10 wt %. In addition, the D / G ratio of the graphene sheet and the graphene contained in the outer carbon coating layer used in Example 2 was 0.2.

[0159] Example 3: Preparation of negative electrode active material

[0160] The negative electrode active material of Example 3 was prepared in the same manner as in Example 1, except that the silicon-based core particles with an inner carbon coating layer and the graphene sheet were mixed in a weight ratio of 97.5:2.5. In this negative electrode active material, the outer carbon coating layer was contained in the negative electrode active material in an amount of 2.5 wt%. In addition, the D / G ratio of the graphene sheet and the graphene contained in the outer carbon coating layer used in Example 3 was 0.2.

[0161] Example 4: Preparation of negative electrode active material

[0162] The negative electrode active material of Example 4 was prepared in the same manner as in Example 1, except that the silicon-based core particles having an inner carbon coating layer and the graphene sheet were mixed at a weight ratio of 80:20. In this negative electrode active material, the outer carbon coating layer was contained in the negative electrode active material in an amount of 20 wt %. In addition, the D / G ratio of the graphene sheet and the graphene contained in the outer carbon coating layer used in Example 4 was 0.2.

[0163] Example 5: Preparation of negative electrode active material

[0164] The negative electrode active material of Example 5 was prepared in the same manner as in Example 1, except that the time for the dispersion to pass through and circulate in the microchannel in the preparation of the graphene sheet of Example 1 was changed to 5 minutes.

[0165] The D / G ratio of graphene contained in the graphene sheet and the outer carbon coating prepared above was 0.03.

[0166] Example 6: Preparation of negative electrode active material

[0167] The negative electrode active material of Example 6 was prepared in the same manner as in Example 1, except that the time for the dispersion to pass through and circulate in the microchannel in the preparation of the graphene sheet of Example 1 was changed to 60 minutes.

[0168] The D / G ratio of graphene contained in the graphene sheet and the outer carbon coating prepared above was 0.3.

[0169] Comparative Example 1: Preparation of negative electrode active material

[0170] The silicon-based core particles having an inner carbon coating layer of Example 1 were used as the negative electrode active material of Comparative Example 1.

[0171] Comparative Example 2: Preparation of negative electrode active material

[0172] <Preparation of graphene sheets>

[0173] The negative active material of Comparative Example 2 was prepared in the same manner as in Example 1, except that the time for the dispersion to pass through and circulate in the microchannel in the preparation of the graphene sheet of Example 1 was changed to 120 minutes.

[0174] The D / G ratio of the graphene sheet prepared above was calculated by Raman spectrum of a Raman spectrometer (D / G ratio=0.45).

[0175] <Preparation of negative electrode active material>

[0176] The negative electrode active material of Comparative Example 2 was manufactured in the same manner as in Example 1, except that the graphene sheet prepared as described above was used. The D / G ratio of the graphene contained in the outer carbon coating layer of Comparative Example 2 was 0.45.

[0177] Comparative Example 3: Preparation of negative electrode active material

[0178] <Preparation of graphene sheets>

[0179] Graphene oxide is formed by the Hummer method known in the art. Specifically, potassium permanganate (KMnO4) is added to an aqueous solution in which graphite, sodium nitrate and sulfuric acid are mixed to form graphene oxide (graphene sheet).

[0180] The D / G ratio of the graphene sheet prepared above was calculated by Raman spectrum of Raman spectrometer (D / G ratio=1). The method of preparing graphene by forming graphene oxide is difficult to control the defects of graphene, so that the D / G ratio is very large.

[0181] <Preparation of negative electrode active material>

[0182] The negative electrode active material of Comparative Example 3 was manufactured in the same manner as in Example 1, except that the graphene sheet prepared as described above was used. The D / G ratio of the graphene contained in the outer carbon coating layer of Comparative Example 3 was 1.

[0183] Experimental example

[0184] <Negative Electrode Manufacturing>

[0185] As the negative electrode material, a mixture of the negative electrode active material prepared in Example 1 and artificial graphite (average particle size (D 50 ): 20 μm).

[0186] The negative electrode material, styrene butadiene rubber as a binder, Super C-65 as a conductive material, and CMC as a thickener were mixed at a weight ratio of 96:2:1:1, and the mixture was added to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry.

[0187] The negative electrode slurry was charged at 3 mAh / cm 2 A loading amount of was coated on one surface of a copper collector (thickness: 15 μm) as a negative electrode collector, roll-pressed, and then dried in a vacuum oven at 130°C for 10 hours to form a negative electrode active material layer (thickness: 60 μm), which was used as the negative electrode according to Example 1 (thickness of the negative electrode: 75 μm).

[0188] Furthermore, each of negative electrodes of Examples 2 to 6 and Comparative Examples 1 to 3 was manufactured in the same manner as in Example 1, except that each of negative electrode active materials of Examples 2 to 6 and Comparative Examples 1 to 3 was used instead of the negative electrode active material of Example 1.

[0189] <Secondary Battery Manufacturing>

[0190] A lithium metal counter electrode was used as the positive electrode.

[0191] A porous polyethylene separator was inserted between the negative electrode and the positive electrode of each of Examples 1 to 6 and Comparative Examples 1 to 3 manufactured above, and an electrolyte was injected thereto to manufacture a coin-type half-cell secondary battery.

[0192] As the above-mentioned electrolyte, a solution prepared by dissolving 0.5 wt % of vinylene carbonate (VC) into a solution in which ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were mixed in a volume ratio of 7:3 and then dissolving LiPF6 therein to a concentration of 1 M was used.

[0193] Experimental Example 1: SEM Photo Evaluation

[0194] exist Figure 1 , a photograph of the negative electrode active material prepared in Example 1 taken by a scanning electron microscope (SEM) is shown.

[0195] refer to Figure 1 , it can be confirmed that an outer carbon coating layer containing graphene is formed on the silicon-based core particles.

[0196] Experimental Example 2: Lifespan Characteristics Evaluation

[0197] <Capacity retention rate evaluation>

[0198] The secondary batteries produced in each of Examples 1 to 6 and Comparative Examples 1 to 3 were evaluated for cycle capacity retention using an electrochemical charge and discharge device.

[0199] The secondary batteries of the examples and comparative examples were charged and discharged under the following experimental conditions.

[0200] First cycle: Charging conditions: CC / CV, 0.1C charging 5mV / 0.005C cut-off, Discharging conditions: CC, 0.1C discharging 1.5V cut-off

[0201] Second cycle: Charging conditions: CC / CV, 0.1C charging 5mV / 0.005C cut-off, Discharging conditions: CC, 0.1C discharging 1.0V cut-off

[0202] For the third cycle or more: Charging conditions: CC / CV, 0.5C charging 5mV / 0.005C cut-off, Discharging conditions: CC, 0.1C discharging 1.0V cut-off

[0203] Thereafter, the capacity retention rate of the secondary battery was evaluated by the following Formula 2.

[0204] [Formula 2]

[0205] Capacity retention rate (%) = {(discharge capacity in the Nth cycle) / (discharge capacity at 1.0 V in the first cycle)}×100

[0206] The capacity retention rate (%) at the 30th cycle is shown in Table 1 below.

[0207] [Table 1]

[0208] Capacity retention rate at the 30th cycle (%) Example 1 91 Example 2 94 Example 3 87 Example 4 88 Example 5 81 Example 6 82 Comparative Example 1 70 Comparative Example 2 73 Comparative Example 3 70

[0209] Referring to Table 1, the negative active material of the Example including the graphene having the D / G ratio according to the present invention as an outer carbon coating component exhibited excellent cycle capacity retention compared to the Comparative Example having an outer carbon coating different from that of the Example.

[0210] Experimental Example 3: Evaluation of High-temperature Storage Capacity Retention Rate

[0211] The high-temperature storage capacity retention ratio of the secondary batteries manufactured in each of Examples 1 to 6 and Comparative Examples 1 to 3 was evaluated.

[0212] The high-temperature storage capacity retention ratio was evaluated by storing the secondary battery in a fully charged state for 4 weeks and performing charge and discharge under the following charge and discharge conditions.

[0213] Thereafter, the high temperature storage capacity retention rate was calculated by the following formula 3, and the results are shown in Table 2.

[0214] [Formula 3]

[0215] Capacity retention rate (%) = {(discharge capacity of the third cycle) / (discharge capacity of the first cycle)}×100

[0216] [Table 2]

[0217] High temperature storage capacity retention rate (%) Example 1 93 Example 2 95 Example 3 89 Example 4 90 Example 5 84 Example 6 83 Comparative Example 1 75 Comparative Example 2 76 Comparative Example 3 75

[0218] Referring to Table 2, the negative active material of the Example including the graphene having the D / G ratio according to the present invention as an outer carbon coating component exhibited excellent high temperature storage characteristics compared with the Comparative Example having an outer carbon coating different from the Example.

Claims

1. A negative electrode active material for a secondary battery, the negative electrode active material for a secondary battery comprising: Silicon-based core particles; and An outer carbon coating is formed on the silicon-based core particle, wherein The outer carbon coating layer includes graphene having a D / G ratio in a Raman spectrum of 0.2 to 0.25, and the D / G ratio in the Raman spectrum is represented by the following Formula 1: [Formula 1] D / G ratio = D band peak intensity / G band peak intensity, The outer carbon coating layer is contained in the negative electrode active material for a secondary battery in an amount of 1 wt % to 25 wt %.

2. The negative electrode active material for a secondary battery according to claim 1, wherein the silicon-based core particle comprises a silicon-based material represented by the following Chemical Formula 1 and at least one metal contained in the silicon-based material and selected from the group consisting of Li, Mg and Al: [Chemical formula 1] Not. x in, In the above Chemical Formula 1, 0≤x<2. 3 . The negative electrode active material for a secondary battery according to claim 2 , wherein the metal is contained in the silicon-based core particle in an amount of 1 wt % to 30 wt %. 4 . The negative electrode active material for a secondary battery according to claim 1 , further comprising an inner carbon coating layer formed between the silicon-based core particle and the outer carbon coating layer.

5. A method for preparing the negative electrode active material for a secondary battery according to claim 1, the method comprising: mixing silicon-based core particles and graphene sheets; as well as The mixture is heat treated. 6 . The method according to claim 5 , wherein the heat treatment is performed by injecting an inert gas at 150° C. to 350° C. into the drying chamber while spraying the mixture into the drying chamber.

7. The method according to claim 5, wherein the graphene sheet is prepared by a method comprising the following steps: (a) forming a dispersion liquid containing a graphite-based material and a dispersant; and (b) allowing the dispersion to continuously pass through a high-pressure homogenizer via an inlet of the high-pressure homogenizer, wherein the high-pressure homogenizer includes an inlet, an outlet, and a microchannel connecting the inlet and the outlet, thereby exfoliating graphene sheets in the graphite-based material.

8. The method according to claim 7, wherein: The dispersion is introduced into the inlet of the high pressure homogenizer under a pressure of 100 bar to 3000 bar and passes through the microchannel.

9. The method according to claim 7, wherein the graphite-based material is plate-like graphite.

10. A negative electrode for a secondary battery, the negative electrode for a secondary battery comprising: a negative electrode current collector; and A negative electrode active material layer is formed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode material, a binder and a conductive material, and the negative electrode material contains the negative electrode active material for a secondary battery according to claim 1.

11. The negative electrode for a secondary battery according to claim 10, wherein: The negative electrode material further comprises a carbon-based active material; and The negative electrode material includes the negative electrode active material for a secondary battery and the carbon-based active material in a weight ratio of 1:99 to 35:

65.

12. A secondary battery, comprising: The negative electrode for a secondary battery according to claim 10; a positive electrode opposite to the negative electrode for the secondary battery; a separator interposed between the positive electrode and the negative electrode for a secondary battery; and Electrolytes.

Citation Information

Patent Citations

  • Negative electrode active material for rechargable lithium battery, method for manufacturing the same, and rechargable lithium battery including the same

    KR1020170074030A

  • Uses of manganese superoxide dismutase with high stability

    KR1020190138874A

  • Silicon negative electrode material and preparation method therefor, negative electrode plate and lithium ion battery

    CN107302082A

  • High-capacity and -stability silicon-carbon anode material and preparation method thereof

    CN109411714A

  • Nonaqueous secondary battery carbon material, nonaqueous secondary battery anode, and lithium ion secondary battery

    JP2013197082A